The Twentieth-Century American City : Problem, Promise, and Reality - Teaford, Jon C. (Book collections on Project MUSE., 2016)
Throughout the twentieth century, the city was deemed a problematic space, one that Americans urgently needed to improve. Although cities from New York to Los Angeles served as grand monuments to wealth and enterprise, they also reflected the social and economic fragmentation of the nation. Race, ethnicity, and class splintered the metropolis both literally and figuratively, thwarting efforts to create a harmonious whole. The urban landscape revealed what was right--and wrong--with both the country and its citizens' way of life. In this thoroughly revised edition of his highly acclaimed book, Jon C. Teaford updates the story of urban America by expanding his discussion to cover the end of the twentieth century and the first years of the next millennium. A new chapter on urban revival initiatives at the close of the century focuses on the fight over suburban sprawl as well as the mixed success of reimagining historic urban cores as hip new residential and cultural hubs. The book also explores the effects of the late-century immigration boom from Latin America and Asia, which has complicated the metropolitan ethnic portrait. Drawing on wide-ranging primary and secondary sources, Teaford describes the complex social, political, economic, and physical development of US urban areas over the course of the long twentieth century. Touching on aging central cities, technoburbs, and the ongoing conflict between inner-city poverty and urban boosterism, The Twentieth-Century American City offers a broad, accessible overview of America's persistent struggle for a better city. Jon C. Teaford is professor emeritus of history at Purdue University. He is the author of Rough Road to Renaissance: Urban Revitalization in America, 1940-1985, The Metropolitan Revolution: The Rise of Post-Urban America, and The American Suburb: The Basics. "Teaford has written an exceptionally useful book for undergraduate teaching. His discussion of American cities in the twentieth century is built around clear interpretive themes that students should quickly recognize and to which they can reasonably be asked to respond... This is a book well designed for undergraduate use." -- History Teacher "A lively, thoughtful, and well-written book that should prove to be exciting for the undergraduate student and useful also for the well-read scholar." -- History "This book has value for all students of modern urban America. Do I plan to use it for my own urban history course? Yes, most definitely." -- Indiana Magazine of History "The book has much to recommend it as a supplementary textbook for a number of urban and historical geography courses." -- Progress in Human Geography.